Coasting related to taxane-induced peripheral neuropathy in patients with breast cancer: a systematic review - Freja L. Kruse; Margrethe B. Bille; Maria E. Lendorf; Susan Vaabengaard; Steffen Birk (Acta Oncologica)
Background and purpose: Chemotherapy-induced peripheral neuropathy (CIPN) is a common dose limiting adverse effect that may be transient or become persistent after the treatment ended. The taxane paclitaxel induces CIPN in 57–83% of patients treated. The neuropathy may debut or progress after the end of treatment (EOT), known as coasting, but little is known about the incidence of this phenomenon. The aim of this review is to examine the incidence and severity of coasting in CIPN in patients with breast cancer.